2018
DOI: 10.2478/jped-2018-0002
|View full text |Cite
|
Sign up to set email alerts
|

E-portfolios and relational space in the early education environment

Abstract: This paper considers the role of eportfolios as an online tool intended to foster greater engagement between parent, teacher and child in early education settings. Drawing on New Zealand based research, I will critically examine the introduction of this technology as more than an addition into already existing ECEC services. Rather, I will highlight the generative impact it has in facilitating new kinds of relations between parents, teachers and managers, within what I term an emergent ‘virtual landscape of EC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 32 publications
0
11
0
5
Order By: Relevance
“…While it is generally accepted that positive engagement between families and ECEC settings is beneficial for children, the meaning and purpose of partnerships, involvement and engagement with families are contested in the literature (Hadley & Rouse, 2018). It is perhaps unsurprising, then, that services may look for new methods of communicating and engaging with families, particularly when both parents are employed and feeling separation anxiety from their young children (Gallagher, 2018). Many of today’s parents, who themselves are digitally literate, are likely to be comfortable with app-based communication.…”
Section: Digital Apps In Ececmentioning
confidence: 99%
“…While it is generally accepted that positive engagement between families and ECEC settings is beneficial for children, the meaning and purpose of partnerships, involvement and engagement with families are contested in the literature (Hadley & Rouse, 2018). It is perhaps unsurprising, then, that services may look for new methods of communicating and engaging with families, particularly when both parents are employed and feeling separation anxiety from their young children (Gallagher, 2018). Many of today’s parents, who themselves are digitally literate, are likely to be comfortable with app-based communication.…”
Section: Digital Apps In Ececmentioning
confidence: 99%
“…Feedback from children and parents is often sought (see Cameron, 2018) by reading observational notes to the child and his or her parents which are frequently accompanied by photographs of moments in the learning process, and then inviting them to comment or add their perspectives before writing up a final version of a learning story. Recent research studies in NZ (e.g., Beaumont-Bates, 2017;Gallagher, 2018;Goodman & Cherrington, 2015Higgins & Cherrington, 2017;Hooker, 2015;Penman, 2014) revealed that such parental contribution can be considerably enhanced through the use of digital learning story portfolios compared to paper-based portfolios, mainly because assessment is accessible in 'real-time' through online portfolios (Goodman & Cherrington, 2015;Hooker, 2015). The rationale for these discussions is not only to authenticate teachers' interpretations of a child's learning but also to provide alternative insights to those of teachers (Carr, 2001;MoE, 2017; see also Snow & Van Hemel, 2008).…”
Section: Recognise -Do You Understand My Story?mentioning
confidence: 99%
“…«Kompik -Kompetenzen und Interessen von Kindern» (Bauer, Krause und Mayr 2012), «PERiK -positive Entwicklung und Resilienz im Kindergartenalltag » (Ulich und Mayr 2007), «Kuno Bellers Entwicklungstabelle» (Beller und Beller 2010), «Baum der Erkenntnis» (Berger und Berger 2006)). Gängige Verfahren zur Aufdeckung von Entwicklungsrisiken sind beispielsweise die «EBD 3-48/48-72 -Entwicklungsbeobachtung und -dokumentation für Kinder von 3-48/48-72 Monate» (Petermann, Petermann, und Koglin 2017, 2018, der «BBK 3-6 -Beobachtungsbogen für 3-6-jährige» (Frey, Duhm und Althaus 2008) und «Validierte Grenzsteine der Entwicklung» (Laewen o.J.). Viernickel und Völkel (2009) empfehlen die Kombination der unterschiedlichen Verfahrenstypen, wobei ein prozessorientiertes Verfahren im Vordergrund stehen und die diagnostischen bestmöglich ergänzend genutzt werden sollten.…”
Section: Verfahren Für Die Dokumentation In Kitasunclassified
“…Beispielsweise könnten, durch Fotos und Videoaufnahmen, Lern-und Bildungsprozesse mithilfe von Apps besonders gut aufgezeigt werden (Kumpulainen und Ouakrim-Soivio 2019). Auch könnten Kinder sowie Eltern besser am Dokumentationsprozess partizipieren und die Kommunikation mit Eltern würde intensiviert (Einarsdóttir 2005;Gallagher 2018;Knauf 2020;Parnell und Bartlett 2012).…”
Section: Die Nutzung Von Dokumentations-apps In Kindertagesstättenunclassified
See 1 more Smart Citation